Beyond Emotional Intelligence A Guide to Accessing Your Full Potential. - Nevarez, S. Michele (John Wiley & Sons, Incorporated, 2022)
Discover the hidden inner workings of your mind so you can break unhelpful habits and set yourself on the path to achieving your full potential. Beyond Emotional Intelligence reveals how our ingrained mental tendencies can either help or hinder us, depending on how conscious we are of their influence over our lives. Whether we seek to set and achieve our desired outcomes, improve our relationships, or live in alignment with what we value most, we need emotional intelligence (EI) to identify and overcome the mental patterns that may be keeping us stuck. In this book, you'll embark on 12 Self-Discoveries that will help you get to know yourself, so you can stop getting in your own way. You'll learn how, with practice, you can retrain your mind to develop new thought patterns that will serve you better as you work toward your life's aspirations. Each of the 12 Self-Discoveries offers unique clues and insights into who we are and why we do what we do. They function as an internal barometer for our triggers, emotional patterns, and mental habits. Ultimately, they provide a clear path to uncover and work with our habits of mind and patterns of action and reaction, giving us the possibility to exercise our own agency at key moments in our lives. Beyond Emotional Intelligence presents the 12 Self-Discoveries framework which provides you with a solid foundation from which you can begin to grow. Discover how your hidden thought patterns are influencing your life and your relationships with others Build Emotional Intelligence as you learn to recognize your reactions, perceptions, and value systems Use the highly regarded 12 Self-Discoveries model to identify your mental roadblocks and remove them with new habits of mind Learn proven methods for influencing your outcomes, de-cluttering your mind, and shift your own awareness This book will be your guide as you embark on a rigorous process of self-discovery as you learn to embrace your inner wisdom and take control of your results.